A atividade discente na universidade: os impactos da produtividade acadêmica na formação dos estudantes - Oliveira, Maísa Aparecida de (2014)
This research examines student activity in university area, focusing a discussion of the impacts of academic productivity in students' education, in which discuss social, ethics and policy university, directed to the interpersonal spaces of socialization, training and performance of students. The academic productivity, as country policy and institutional culture, became polo generator of university reform slavishly follow the market, revealing the marketisation of science and technological innovation. The university legitimizes and reproduces relations of social domination, focusing on how the school trajectory student influences the dynamic of their activities at the university, conditioning the choices and attitudes in developing their personal and professional formation. 120 students of 12 undergraduate courses divided in Science Centers related to Biological, Human and Physical areas of UFSCar participated in the survey and responded to a questionnaire and subsequently 10 % of students perform a semistructured interview. The qualitative data analysis was performed using the categorization of semantic contents based on theoretical contributions from critical perspectives process. The survey results indicate that socialization at the university is produced from which the student brings himself and at the same time, it is producer of training student. The relationships established by students in the university context are permeated by academic goal, identified impersonally, as found by the distance between students themselves and between students and teachers, besides low level of student participation in university groups. This issue indicates the expansion of regulated individualism in pragmatic and utilitarian logic. Among the activities performed in the student course, the highest participation rate concentrated at scientific meetings and in junior reseacher program, which supports the conception of the overvaluation of the research. Students consider that research positively affects their training, contributing to their intellectual and professional growth, and fill possible gaps in their training to provide the interaction between theory and practice. The choice of students in academic activities, legitimized by the university, is delimited by the instrumentality of school success, achieved through participation in activities considered profitable, constitutive category for the inclusion and recognition of the student in the academic field. We conclude that students have incorporated the practice of production scientific knowledge that follows the logic of intensified and productivist work of university teachers, guided by the marketisation of knowledge in the context of neoliberal policies. In this sense, the activity of the student, as a social subject, reduced to the academic and scientific activities, with few opportunities for rest and recreation, noting a significant decrease of their social experiences, evidenced in the emotional, social, political, cultural and physical relations.